Prevalence of major depressive disorder among hemodialysis patients compared with healthy people in Japan using the Structured Clinical Interview for DSM-IV - Tomita T; Yasui-Furukori N; Sugawara N; Ogasawara K; Katagai K; Saito H; Sawada K; Takahashi I; Nakamura K (Neuropsychiatric Disease and Treatment)
Tetsu Tomita,1 Norio Yasui-Furukori,1 Norio Sugawara,1,2 Kohei Ogasawara,3 Koki Katagai,3 Hisao Saito,4 Kaori Sawada,5 Ippei Takahashi,5 Kazuhiko Nakamura1 1Department of Neuropsychiatry, Graduate School of Medicine, Hirosaki University, Hirosaki, Japan; 2Aomori Prefectural Center for Mental Health and Welfare, Aomori, Japan; 3School of Medicine, Hirosaki University, Hirosaki, Japan; 4Department of Urology, Oyokyo Kidney Research Institute, Hirosaki, Japan; 5Department of Social Medicine, Graduate School of Medicine, Hirosaki University, Hirosaki, Japan Background: We investigated the prevalence of depression in hemodialysis (HD) patients using the Center for Epidemiologic Studies for Depression (CES-D) scale and the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (SCID) and compared the rates with those of community dwelling people in Japan.Patients and methods: A total of 99 patients undergoing HD were recruited. Blood sampling was performed no later than 2 weeks prior to assessment. As a reference group for SCID and CES-D evaluation, 404 age- and sex-matched healthy controls who had participated in the Iwaki Health Promotion Project were included in this study. The SCID and the CES-D scale were administered to all participants to diagnose their depression. Participants who met the criteria of a major depressive episode according to the SCID were classified as SCID depression and the participants whose CES-D score was 16 or higher were classified as CES-D depression.Results: Ninety-nine HD patients completed the evaluation and data collection. There were no significant differences in age, sex, or CES-D scores between HD patients and controls. There were 12 cases of SCID depression in HD patients and four cases in controls. There was a significant difference between HD patients and controls in the prevalence of SCID depression. There were no significant differences between the two groups with regard to demographic or clinical data. There were 19 HD patients and 24 controls who showed CES-D depression. There was no significant difference between HD patients and controls in the prevalence of CES-D depression. There was a significant difference in potassium level between the two groups, but there were no significant differences in any of the other items.Conclusion: There were significantly more HD patients showing SCID depression than controls in the present study. In clinical settings, the SCID might be useful in surveying cases of depression detected by screening tools among HD patients. Keywords: depression, Center for Epidemiologic Studies for Depression, Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, diagnosis